MMP-9/Gelatinase B Degrades Immune Complexes in Systemic Lupus Erythematosus - Ugarte-Berzal, Estefania; Boon, Lise; Martens, Erik; Rybakin, Vasily; Blockmans, Daniel; Vandooren, Jennifer; Proost, Paul; Opdenakker, Ghislain (Frontiers in Immunology, 2019)
Systemic Lupus Erythematosus (SLE) is a common and devastating autoimmune disease, characterized by a dysregulated adaptive immune response against intracellular antigens, which involves both autoreactive T and B cells. In SLE, mainly intracellular autoantigens generate autoantibodies and these assemble into immune complexes and activate the classical pathway of the complement system enhancing inflammation. Matrix metalloproteinase-9 (MMP-9) levels have been investigated in the serum of SLE patients and in control subjects. On the basis of specific studies, it has been suggested to treat SLE patients with MMP inhibitors. However, some of these inhibitors induce SLE. Analysis of LPR-/-MMP-9-/- double knockout mice suggested that MMP-9 plays a protective role in autoantigen clearance in SLE, but the effects of MMP-9 on immune complexes remained elusive. Therefore, we studied the role of MMP-9 in the clearance of autoantigens, autoantibodies and immune complexes and demonstrated that the lack of MMP-9 increased the levels of immune complexes in plasma and local complement activation in spleen and kidney in the LPR-/- mouse model of SLE. In addition, we showed that MMP-9 dissolved immune complexes from plasma of lupus-prone LPR-/-/MMP-9-/- mice and from blood samples of SLE patients. Surprisingly, autoantigens incorporated into immune complexes, but not immunoglobulin heavy or light chains, were cleaved by MMP-9. We discovered Apolipoprotein-B 100 as a new substrate of MMP-9 by analyzing the degradation of immune complexes from human plasma samples. These data are relevant to understand lupus immunopathology and side-effects observed with the use of known drugs. Moreover, we caution against the use of MMP inhibitors for the treatment of SLE.